The domain-general and domain-specific cognitive profiles in high and low-achieving Chinese L2 learners - Xiao, Qing; Shi, Yue; Cheng, Dazhi (Frontiers in Psychology, 2025)
Although both general cognitive and domain-specific skills are important for Chinese L2 learning, it remains unclear whether high and low-achieving Chinese L2 learners differ in specific cognitive abilities. This study examines both domain-general and domain-specific cognitive profiles in high and low-achieving Chinese L2 learners. Sixty-four Chinese L2 learners from Southeast Asia were categorized into high-achieving group and low-achieving group based on academic performance and teacher evaluations. The study assessed general cognitive functions, including working memory, attention, and phonological processing, as well as domain-specific skills such as morphological awareness. The results showed that low-achieving Chinese L2 learners performed poorly in phonological processing tasks such as verbal working memory and pitch matching. They also underperform in morphological awareness tasks such as nonword identification and homophone judgment. These findings demonstrated the critical role of both phonological processing and morphological awareness in Chinese L2 learning suggesting potential interventions targeting these cognitive areas to improve learning outcomes for low-achieving Chinese L2 learners.